Assessing the Relationship between Students Attitude and Online Shopping - Rimal, Pratibha; Bhattarai, Prakriti; Pokhrel, Pranit; Pradhananga, Prakriti; Shahi, Preeti; Magar, Preety Rana; Ghimire, Jagadish Chandra (Baneshwor Campus Journal of Academia, 2024)
This study investigates the relationship between attitudes of youth towards online shopping, focusing on BBS students at Shanker Dev Campus (SDC). The research is motivated by the growing significance of online shopping among the youth demographic and the need to understand the underlying factors driving their attitudes. Drawing on a sample of 124 BBS students, data was collected using a questionnaire and analyzed through descriptive statistics, correlation analysis, and hypothesis testing. The findings reveal significant relationships between trust, convenience, price, digital literacy, and attitudes towards online shopping among the surveyed students. Trust and convenience emerged as key factors positively associated with online shopping attitudes, while price sensitivity and digital literacy also played significant roles. Moreover, the study highlights the interconnected nature of these factors, suggesting that improvements in one area can positively influence others.